Audit Quality In Libya: Perceptions Of External Auditors - Fuad Elmahedi H. Bashir
Audit quality has been a focus of interest and research in advanced countries for several decades given the role of auditors’ reports in the decision- making process used by investors. Despite the importance and the need for quality, there is no consensus on how audit quality should be measured. The present study attempts to develop a framework for audit quality. The objective is to obtain an insight into auditors’ perception of audit quality factors that relate to audit team factors, audit office factors and external environment audit factors which contribute to enhance audit quality. The conceptual model of this study is based on agency theory, stakeholder theory, and contingency theory .The variables of study are classified into three main groups: the first group is audit team factors including independence, continuous education and training, experience and professional conduct. The second group is audit office factors including planning of audit processes, supervision, specialization in the industry, and audit office size. The third group is audit environment including professional bodies, laws and regulations, and recognized standards. This study also examines the moderating effect of the external environment audit in the relationship between (1) audit team factors or (2) audit office factors, and audit quality. A total of 530 questionnaires were distributed to the Libyan Independent Auditors. The number of usable questionnaires was 251, yielding 47.36 percent response rate. Interviews were also conducted to gain a more in-depth understanding of the empirical results. Based on multiple regression analysis, the results indicate that both (1) audit team factors, and (2) audit office factors are significantly related to audit quality. The findings also indicate that the external environment audit moderates the relationship between audit team factors and audit quality while it does not moderate the relationship between audit office factors and audit quality. Overall, the findings of the study are expected to provide a Libyan audit firm with the importance of tackling the issue of audit quality, and to contribute in strengthening the capacity of audit firm when the recommendations are implemented